Peran UMKM dalam Penerapan SDGs (Sustainable Development Goals) di Yayasan Bina Umat Kelapa Dua - Ratna Mira Yojana; Dadang Surjasa; Yuli Kurnia Ningsih; Dedy Sugiarto; Dadan Umar Daihani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2023)
The Sustainable Development Goals (SDGs) are targets agreed upon by members of the United Nations in 2015. Indonesia is a member of the United Nations committed to making SDGs a priority in National Development. Micro, Small and Medium Enterprises (MSMEs) in Indonesia are one of the economic heroes which are the government's priority in national economic development. The government is making various efforts to develop MSMEs because technology and capital support are one of the keys to the success of MSMEs. The Bina Umat Kelapa Dua Foundation (YBUK) Association is a collection of several MSMEs in the Kelapa Dua area who want to continue developing MSMEs in their area. However, they experienced several obstacles, including the problem of limited knowledge of technology and business capital. The Master of Industrial Engineering at Trisakati University and the management of the YBUK Association jointly held SDGs socialization activities in Community Service (PKM) activities as the first step in helping MSMEs develop their businesses. The theme taken is socio-economic, business and energy in MSME scale sdgs. The enthusiasm of the PKM participants was quite high, and they hoped that similar activities would be held with wider participants.